2017
DOI: 10.1021/acs.energyfuels.7b00850
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Ash Composition (Ca, Fe, and Ni) on Petroleum Coke Ash Fusibility

Abstract: Ash fusion behavior is closely associated with ash-related problems including fouling, sintering, and slagging, which results in a negative effect on the utilization of petroleum coke (petcoke). Petcoke ash contains high levels of vanadium (V), nickel (Ni), iron (Fe), and calcium (Ca). The chemical composition of ash plays an intrinsic role in determining ash fusibility. To better understand the modification mechanism of the ash fusion temperatures (AFTs), this study investigates the influences of ash composit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(7 citation statements)
references
References 42 publications
(65 reference statements)
0
7
0
Order By: Relevance
“…Ni 2 SiO 4 was found by Li et al in petcoke ash slag obtained under oxidizing conditions [13,14]. [13,14]. In comparison with Figure 8, the plots in Figure 13 show that drop in Al 2 O 3 (solid), occurs at lower temperatures.…”
Section: Resultsmentioning
confidence: 59%
See 1 more Smart Citation
“…Ni 2 SiO 4 was found by Li et al in petcoke ash slag obtained under oxidizing conditions [13,14]. [13,14]. In comparison with Figure 8, the plots in Figure 13 show that drop in Al 2 O 3 (solid), occurs at lower temperatures.…”
Section: Resultsmentioning
confidence: 59%
“…Ni 2 SiO 4 is present in the thermodynamic calculation results. Ni 2 SiO 4 was found by Li et al in petcoke ash slag obtained under oxidizing conditions [13,14]. [13,14].…”
Section: Resultsmentioning
confidence: 79%
“…The results (Figure 2, Table 3) confirmed that large quantities of organic matter were removed through annealing; however, 11.73% of residues remained even after annealing at 2700 °C. EDS mapping ( Figure 3) was performed to determine the composition of the residue Among the metal components, a large quantity of vanadium was observed in the petroleum coke soot [19][20][21]. Many prior studies have suggested various physical and chemical methods to remove this metal.…”
Section: Resultsmentioning
confidence: 99%
“…The ash compositional differences between petcoke and coal may cause different mineral transformation behaviors because of the presence of V and Ni in petcoke. We have investigated the effect of petcoke ash composition (V 2 O 5 , NiO, CaO, and Fe 2 O 3 ) on ash fusion behaviors in previous researches. , The acidic ash constituents SiO 2 , Al 2 O 3 , and TiO 2 are generally considered to act as receptors (network formers) and the basic oxides CaO, Fe 2 O 3 , Na 2 O, K 2 O, and MgO as oxygen donators (network modifiers) . The base-acid ratio R defined as (CaO + Fe 2 O 3 + Na 2 O + K 2 O + MgO)/(SiO 2 + Al 2 O 3 + TiO 2 ), which is the same as the effect of (SiO 2 + Al 2 O 3 ) ratio, has been used to rank the propensity of melting, fouling, and slagging. Moreover, the S/A ratio is also an important factor for the initial evaluations of ash fusibility. , In this work, both S/A and (SiO 2 + Al 2 O 3 ) ratios are considered to characterize the influences of SiO 2 and Al 2 O 3 on petcoke ash fusion behaviors, which is expected to provide a guide for the efficient utilization of petcoke.…”
Section: Introductionmentioning
confidence: 99%
“…We have investigated the effect of petcoke ash composition (V 2 O 5 , NiO, CaO, and Fe 2 O 3 ) on ash fusion behaviors in previous researches. 24,25 The acidic ash constituents SiO 2 , Al 2 O 3 , and TiO 2 are generally considered to act as receptors (network formers) and the basic oxides CaO, Fe 2 O 3 , Na 2 O, K 2 O, and MgO as oxygen donators (network modifiers). 26 The base-acid ratio R defined as (CaO + Fe 2 O 3 + Na 2 O + K 2 O + MgO)/ (SiO 2 + Al 2 O 3 + TiO 2 ), which is the same as the effect of (SiO 2 + Al 2 O 3 ) ratio, has been used to rank the propensity of melting, fouling, and slagging.…”
Section: Introductionmentioning
confidence: 99%